Efektivitas Pelajaran PAI Terhadap Pembinaan Akhlaq Dan Disiplin Siswa SMA Negeri 2 Percontohan Karang Baru Kabupaten Aceh Tamiang - Muhammad Wahyudi (Universitas Islam Negeri Sumatera Utara, 2019)
This study uses qualitative methods. Data collection research using the techniques of observation, interview, and study the documents. The findings in this study are: 1) the effectiveness of subject Islamic studies towards the construction of akhlaq and discipline students succeed, this is due to the charge contained in the subjects of Islamic religious education contains moral education and teachings that are capable of forming akhlaq and discipline of students. 2) factors that affect students and disciplines including akhlaq conditions of the families of the students, where most of the parents of students at work so that students may be less attention from parents, and students who are less able to attention at home, the the school gives a good through school activities mainly Islamic Spiritual activities (Rohis). 3) attempts the construction of akhlaq and discipline do SMA Negeri 2 Pilot Coral New Aceh Tamiang Regency, the existence of an Apple in the morning that can assist students in building akhlaq and discipline. 4) existence of factor endowments and a barrier in the process of effectiveness of educational subjects in an Islamic akhlaq coaching and discipline against SMAN 2 Pilot Coral New Aceh Tamiang Regency of which constituents i.e. teacher Factors Islamic religious education lessons that are already very good, and laboratory readings means already owned, as well as a factor of participation of students in a variety of activities.